Promoting rhinoceros welfare during transit: veterinarians' perspectives on transportation practices - Macha ES; Meyer LCR; Leiberich M; Hofmeyr M; Hooijberg EH (Medpharm Publications on behalf of the South African Veterinary Association, 2024)
Despite translocation being a useful conservation strategy in rhinoceros management, morbidities and mortalities occurring during transportation pose a significant concern to rhinoceros managers, veterinarians, and scientists. The objectives of this study were to better understand the effects of transport on rhinoceros and to gain insights from veterinarians involved in rhinoceros translocations about current practices and potential interventions that could improve welfare. A weblink and QR code to an online questionnaire with a total of 46 questions in Google Forms was sent to veterinarians who had experience in African rhinoceros transportation, through personal emails and social network forums. Results demonstrated that despite dehydration and negative energy balance being reported as the major causes of morbidities and mortalities during transport and post-release, most veterinarians (30/35; 86%) involved in rhinoceros translocation did not offer water, parenteral fluids, or feed to transported animals, for logistical reasons and the knowledge or perception of rhinoceros' resistance to taking ad lib food and water during transport. However, 52% (15/29) and 41% (15/34) of participants suggested that parenteral fluids could be used as an intervention to mitigate dehydration and negative energy balance respectively. To reduce stress, 94% (33/35) of respondents suggested the use of tranquilisers and sedatives. This study is the first to systematically investigate and report on practices by veterinarians involved in rhinoceros translocations globally. The study highlights that further research is required to explore optimal and pragmatic techniques in the field to mitigate reported welfare challenges in rhinoceros during transport.
Keywords: rhinoceros; welfare; transport; survey; veterinarian